Performance and emission control of using steam injection on medium-speed marine diesel engine running with biodiesel fuel - Wan Mohd Noor, Che; Rizalman, Mamat; Muhammad Yusri, Ismail; Wan Nurdiyana, Wan Mansor; Sheikh, Alif (Akademi Baru, 2021)
Biodiesel fuel has been categorized as one of the promising renewable energy and at the same time can reduce our dependence on fossil fuels. Yet despite its many advantages, literature studies report that engines running with biodiesel fuel produce slightly less power and higher NOx gas emissions compared to standard diesel fuel. One of the possible ways to reduce NOx gas from marine engines running on biodiesel fuel is by injecting steam water into the air intake engine system. Therefore, this study attempts to investigate the effect of steam injection incorporated with biodiesel fuel on the performance and emissions of marine diesel engines. Experiments were conducted on medium-speed Cummins marine engines using biodiesel blends with concentrations of 10%, 20%, and 30%. The results show that the use of steam does not have a significant effect on the torque and power of the marine engine. However, steam injection methods have successfully reduced the emissions of hazardous gases of nitrogen oxide and carbon monoxide by 37.2% and 66.7%, respectively. Furthermore, fuel consumption rate is also more economical as shown by the BSFC value decreasing up to 15.2%. Overall, the steam injection method can compensate for the lack of performance found in biodiesel fuel when used on marine diesel engines.